Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the length of the longer leg of a right triangle where the hypotenuse [tex]\( h \)[/tex] is three times as long as the shorter leg, labeled as [tex]\( m \)[/tex], we follow these steps:
1. Identify the sides of the triangle:
- The shorter leg is [tex]\( a = m \)[/tex].
- The hypotenuse is [tex]\( h = 3m \)[/tex].
2. Use the Pythagorean theorem, which states [tex]\( a^2 + b^2 = c^2 \)[/tex], to find the length of the longer leg [tex]\( b \)[/tex]:
[tex]\[ a^2 + b^2 = c^2 \][/tex]
Given:
[tex]\[ a = m, \quad c = 3m \][/tex]
Substitute these into the Pythagorean theorem:
[tex]\[ m^2 + b^2 = (3m)^2 \][/tex]
Simplify the right side:
[tex]\[ m^2 + b^2 = 9m^2 \][/tex]
Isolate [tex]\( b^2 \)[/tex] by subtracting [tex]\( m^2 \)[/tex] from both sides:
[tex]\[ b^2 = 9m^2 - m^2 \][/tex]
Simplify the equation:
[tex]\[ b^2 = 8m^2 \][/tex]
Take the square root of both sides to solve for [tex]\( b \)[/tex]:
[tex]\[ b = \sqrt{8m^2} \][/tex]
Simplify the square root:
[tex]\[ b = \sqrt{4 \cdot 2 \cdot m^2} = \sqrt{4} \cdot \sqrt{2} \cdot \sqrt{m^2} = 2 \cdot \sqrt{2} \cdot m = 2\sqrt{2}m \][/tex]
Therefore, the length of the longer leg in terms of [tex]\( m \)[/tex] is:
[tex]\[ \boxed{2\sqrt{2}m} \][/tex]
1. Identify the sides of the triangle:
- The shorter leg is [tex]\( a = m \)[/tex].
- The hypotenuse is [tex]\( h = 3m \)[/tex].
2. Use the Pythagorean theorem, which states [tex]\( a^2 + b^2 = c^2 \)[/tex], to find the length of the longer leg [tex]\( b \)[/tex]:
[tex]\[ a^2 + b^2 = c^2 \][/tex]
Given:
[tex]\[ a = m, \quad c = 3m \][/tex]
Substitute these into the Pythagorean theorem:
[tex]\[ m^2 + b^2 = (3m)^2 \][/tex]
Simplify the right side:
[tex]\[ m^2 + b^2 = 9m^2 \][/tex]
Isolate [tex]\( b^2 \)[/tex] by subtracting [tex]\( m^2 \)[/tex] from both sides:
[tex]\[ b^2 = 9m^2 - m^2 \][/tex]
Simplify the equation:
[tex]\[ b^2 = 8m^2 \][/tex]
Take the square root of both sides to solve for [tex]\( b \)[/tex]:
[tex]\[ b = \sqrt{8m^2} \][/tex]
Simplify the square root:
[tex]\[ b = \sqrt{4 \cdot 2 \cdot m^2} = \sqrt{4} \cdot \sqrt{2} \cdot \sqrt{m^2} = 2 \cdot \sqrt{2} \cdot m = 2\sqrt{2}m \][/tex]
Therefore, the length of the longer leg in terms of [tex]\( m \)[/tex] is:
[tex]\[ \boxed{2\sqrt{2}m} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.